Analysis of hospitalization expenses of 610 HIV/AIDS patients in Nantong, China - Xun Zhuang; Yujia Chen; Zunyou Wu; Sarah Robbins Scott; Renfei Lu; Zhengcheng Xu; Yuhui Yu; Wei Wang; Luyao Cao; Yuanyuan Liang; Gang Qin; Meiyin Zou (BMC, 2020)
Abstract Background The goal of this study was to describe the expenses related to human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) management and care in Nantong Infectious Disease Hospital from October 2013 through June 2017. Methods The information of 610 HIV/AIDS inpatients were collected from the Electronic Medical Record System of the hospital. Univariate and path analysis were employed to evaluate the association between hospitalization expense and its related factors. Results The average hospitalization expenses per person was 5454 RMB (Renminbi, the currency of China, about $808 USD) and 23,555 RMB (about $3489 USD), respectively for HIV/AIDS patients. The average length of hospital stay was 10.0 ± 5.5 days for HIV patients and 21.7 ± 12.4 days for AIDS patients. For HIV patients, laboratory test fees constituted 37.46% of total expenses; while drug fees accounted for the largest proportion for AIDS patients. Path analysis indicated that the length of hospital stay was the most important factor affecting total expenses (total path coefficient = 0.563 for HIV patients and 0.649 for AIDS patients). Total expenses for HIV-infected females was higher than that of males (total path coefficient = 0.217), and the more complications led to higher expenses for AIDS patients. Conclusions Though antiretroviral therapy (ART) is provided for free in China, associated medical care, particularly hospitalizations and fees, continue to drive up the medical costs of patients living with HIV and AIDS. Understanding the factors influencing these costs are crucial for determining policies and strategies that can reduce the economic burden of HIV/AIDS patients in China.